#TITLE_ALTERNATIVE# - Yunita Wijaya (nim: 101 03 035), Madona
Abstract: Perron Frobenius Theory is one of the most elegant theory in algebra about the characteristic of nonnegative matrices based on its spectral property. Its application can be obtained for stochastic matrix. Through this theory, we can derive and proof some properties of the limiting distribution of stochastic matrix. Specifically, we will see the limiting distribution of transition matrix of Markov chain. Besides, we can also interpret its meaning of the limiting distribution.